2019
DOI: 10.1097/md.0000000000016911
|View full text |Cite
|
Sign up to set email alerts
|

Lung abscess by Actinomyces odontolyticus and Parvimonas micra co-infection presenting as acute respiratory failure

Abstract: Rationale:Actinomyces odontolyticus and Parvimonas micra are very rare causative organisms of lung abscess and acute respiratory failure.Patient concerns:A 49-year-old male patient visited the emergency room with a complaint of sudden onset of shortness of breath, and he developed acute respiratory failure rapidly.Diagnosis:An abscess in the left lower lung field was diagnosed on the computed tomography scan of chest.Interventions:Immediate treatment with intravenous antibiotics was initiated along with a pigt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…As the presenting symptoms in these patients were non-specific (e.g., fever, shake, and chills), thorough searches for the primary source of bacteremia may not have been carefully conducted in these 9 cases. In 27 literature cases, P. micra bacteremia were also frequently associated with oropharyngeal infection (7/27, 25.9%) and GIT infection (3/27, 11.1%) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Other common infectious diseases of P. micra in the literature cases were spondylodiscitis (8/27, 29.6%), intra-abdominal abscess (4/27, 14.8%), IE (3.27, 11.1%), and septic pulmonary emboli (3/27, 11.1%) which is inconsistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…As the presenting symptoms in these patients were non-specific (e.g., fever, shake, and chills), thorough searches for the primary source of bacteremia may not have been carefully conducted in these 9 cases. In 27 literature cases, P. micra bacteremia were also frequently associated with oropharyngeal infection (7/27, 25.9%) and GIT infection (3/27, 11.1%) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Other common infectious diseases of P. micra in the literature cases were spondylodiscitis (8/27, 29.6%), intra-abdominal abscess (4/27, 14.8%), IE (3.27, 11.1%), and septic pulmonary emboli (3/27, 11.1%) which is inconsistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…micra is a fastidious, anaerobic, gram-positive coccus that is found in healthy human oral and gastrointestinal flora (10). Previous studies have reported that P. micra is involved in lung abscesses, iliopsoas abscesses, gastric carcinogenesis and infections of the periodontal area, soft tissue, bone and joints (11)(12)(13)(14). Currently, based on metagenomic or 16S RNA sequencing analysis, numerous studies have revealed the relationship between P. micra and CRC (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The scenario highlights the high occurrence of potentially virulent pathogens, which can contribute to severity of lung infection in Coronavirus Disease 2019 patients admitted to intensive care units. Moreover, the prevalence of respiratory pathogens observed in COVID-19 patients analyzed can be orchestrated mainly by the complex and distinct immune events in response to lung damage, as well as by the ecological model proposed by Dickson and collaborators (2014, 2015) ( 26, 25 ), which indicate that several lung diseases can alter the growth of local microbiota, leading to an increase in bacterial abundance. A cellular model to explain the bacterial species described in our study correlated to processes that aggravate COVID-19 is presented (Figure 3).…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, an association of co-infection by A. odontolyticus and P. micra or Streptococcus spp . to lung abscess and acute respiratory failure was reported ( 26, 27 ). Although respiratory disease caused by these commensals is a rare event, their presence in individuals with compromised immune responses should not be neglected.…”
Section: Resultsmentioning
confidence: 99%